Clinical Features and Gene Mutation Analysis of Congenital Thrombotic Thrombocytopenic Purpura in Neonates - Wang, Jiali; Zhao, Li (Frontiers in Pediatrics, 2020)
Congenital thrombotic thrombocytopenic purpura (TTP) is a rare hereditary disease with a high mortality rate; however, improved patient survival is possible with prompt diagnosis and treatment. The clinical features and mutation sites of a disintegrin and metalloproteinase with thrombospondin motifs 13 (ADAMTS13) in congenital TTP were analyzed in a neonate with suspected congenital TTP. High-throughput sequencing, polymerase chain reaction, and Sanger sequencing were utilized for screening of genes related to thrombocytopenic diseases and ADAMTS13 gene mutation testing on blood samples from the neonate and the parents. Domestic and foreign literature reporting the clinical features and variants of ADAMTS13 in neonates with congenital TTP were retrieved, compared, and analyzed. The patient in this case was a girl who had been born for 1 h and admitted to the hospital due to “dyspnea for 1 h.” Routine blood tests on admission revealed profound thrombocytopenia. She quickly developed symptoms of systemic hemorrhage and eventually died. The neonate had two older sisters who had died of idiopathic thrombocytopenia and hemorrhage within 24 h of birth. Genetic testing showed that the neonate harbored a compound heterozygous mutation in ADAMTS13, c.1187G>A/c.1595G>T, which is a novel variant. Of the 12 cases (1 case in China and 11 cases in other countries) of congenital TTP in neonates that have been reported globally, ADAMTS13 mutation analysis was only performed in eight neonates. Common clinical manifestations included dyspnea of unknown etiology, bruising, jaundice, hemorrhage, and thrombocytopenia. Hence, the current case contributes to our understanding of the clinical manifestations and types of variants in neonates with congenital TTP. Our results demonstrate the efficacy of high-throughput sequencing technology in genetic testing of neonates suspected with congenital TTP and have revealed a novel compound missense mutation in ADAMTS13 that has not been reported in China or elsewhere.